Solid bolt fixation of the medial column in Charcot midfoot arthropathy - Wiewiorski, Martin; Yasui, Tetsuro; Miska, Matthias; Frigg, Arno; Valderrabano, Victor (The journal of foot and ankle surgery, 2013)
Charcot medial column and midfoot deformities are associated with rocker bottom foot, recurrent plantar ulceration, and consequent infection. The primary goal of surgical intervention is to realign and stabilize the plantar arch in a shoe-able, plantigrade alignment. Different fixation devices, including screws, plates, and external fixators, can be used to stabilize the Charcot foot; however, each of these methods has substantial disadvantages. To assess the effectiveness of rigid, minimally invasive fixation of the medial column and midfoot, 8 cases of solid intramedullary bolt fixation for symptomatic Charcot neuroarthropathy were reviewed. The patients included 6 males (75%) and 2 females (25%), with a mean age of 63 (range 46 to 80) years. The Charcot foot deformity was caused by diabetic neuropathy in 7 cases (87.5%) and alcoholic neuropathy in 1 (12.5%). The mean duration of postoperative follow-up period was 27 (range 12 to 44) months. The mean radiographic correction of the lateral talar-first metatarsal angle was 15° (range 3° to 19°), and the mean radiographic correction of the dorsal midfoot dislocation was 9 (range −4 to 23) mm. The mean loss of correction of the lateral talar-first metatarsal angle and midfoot dislocation after surgery was 7° (range 0° to 26°) and 1 (range 0 to 7) mm, respectively. No bolt breakage was observed, and no cases of recurrent or residual ulceration occurred during the observation period. Bolt removal was performed in 3 cases (37.5%), 2 (25%) because of axial migration of the bolt into the ankle joint and 1 (12.5%) because of infection. The results of the present review suggest that a solid intramedullary bolt provides reasonable fixation for realignment of the medial column in cases of Charcot neuroarthropathy.